Acute effects of a walking activity on plantar pressure in children with obesity - Flavius Augusto Pinto Cunha; Rodrigo Jerônimo Santos; Paula Ribeiro Mesquita; Ana Cristina de David (Universidade Federal de Santa Catarina, 2021)
Children with obesity present greater foot loads during walking when compared to eutrophic ones. However, the acute effects of a moderate walking on the distribution of plantar pressure in children with obesity are still incipient in the literature. Our aim was to verify the acute effects of six-minute walk test on plantar pressure in obese and eutrophic children. A pressure platform was used to record plantar pressure during walking for 62 children (37 girls), aged 7-10 years old, before and after the six-minute walk test. Children were divided into an obese group - OB (n = 20), and an eutrophic group - EU (n = 42). Peak plantar pressure (PPP), maximum force (MF), and contact area (CA) were assessed in three trials during walking at a comfortable speed. The analyses were performed in five plantar regions: rearfoot, midfoot, forefoot, hallux, and toes. For the PPP was higher under the midfoot region of the OB group after walking. In the comparison between groups, PPP, MF, and CA were higher for the OB group for most regions. We concluded that, after a moderate walking activity, children with obesity experience an increase in plantar loads, especially under the midfoot, which can bring greater discomfort and risk of injuries.